Implementasi Metode Drill dalam Pembelajaran Dribble Bola Basket untuk Meningkatkan Hasil Belajar Siswa - Imas Masitoh; Abduloh Abduloh; Rolly Afrinaldi (Jurnal Literasi Olahraga, 2021)
Abstract The purpose of this study is to improve basketball dribble learning outcomes for class XI students in semester 1 of the 2020/2021 academic year in physical learning subjects through the implementation of drill procedures. From the research results, it can be concluded that the implementation of the Drill method can improve student learning outcomes in physical learning subjects. From this research, it is recommended that teachers look for new innovations that can trigger the education process to be more meaningful. Keywords: drill method, basketball dribble learning, learning outcomes